Community Engagement in a School of Education - Debora Scheffel; Renee Lizcano (Journal of Scholarly Engagement)
A School of Education has a unique opportunity to engage with their local and larger communities. This paper details how one School of Education within a private, religious university works to serve and learn from others through three different initiatives. These include: serving in elected office, creating professional development opportunities for educators and administrators across the state, and developing and implementing a research study involving a reading clinic for local elementary students and their families. We discuss how we have worked to inspire change to lead to improvements in society and the different methods we employed to lead to that change. We conclude by reflecting upon the benefits we have seen so far and describe our plans for community engagement in the future.